Rapid CO2 Release From Eroding Permafrost in Seawater. Issue 20 (29th October 2019) - Tanski, G.; Wagner, D.; Knoblauch, C.; Fritz, M.; Sachs, T.; Lantuit, H.
Abstract: Permafrost is thawing extensively due to climate warming. When permafrost thaws, previously frozen organic carbon (OC) is converted into carbon dioxide (CO2 ) or methane, leading to further warming. This process is included in models as gradual deepening of the seasonal non‐frozen layer. Yet, models neglect abrupt OC mobilization along rapidly eroding Arctic coastlines. We mimicked erosion in an experiment by incubating permafrost with seawater for an average Arctic open‐water season. We found that CO2 production from permafrost OC is as efficient in seawater as without. For each gram (dry weight) of eroding permafrost, up to 4.3 ± 1.0 mg CO2 will be released and 6.2 ± 1.2% of initial OC mineralized at 4 °C. Our results indicate that potentially large amounts of CO2 are produced along eroding permafrost coastlines, onshore and within nearshore waters. We conclude that coastal erosion could play an important role in carbon cycling and the climate system. Plain Language Summary: The permanently frozen soils of the Arctic, known as permafrost, store large amounts of organic carbon, which accumulated over millennia due to slow decomposition in the cold Arctic regions. With climate warming this frozen organic carbon reservoir thaws and microbes recycle it quickly into greenhouse gases, which in turn support further warming. A slow and continuous thaw is currently used in models to project future greenhouse gas release from permafrost. Yet along the rapidly eroding coastlines of the Arctic Ocean, which make up 34% of the Earth's coastlines, whole stretches of the coast simply collapse, sink or slide into the ocean, including the previously frozen organic carbon. We simulated greenhouse gas release in response to coastline collapse in a laboratory experiment by simply mixing permafrost with seawater. We show that large amounts of carbon dioxide are being produced during the Arctic open‐water season. Our study indicates that eroding permafrost coasts in the Arctic are potentially a major source of carbon dioxide. With increasing loss of sea ice, longer open‐water seasons, and exposure of coasts to waves, we highlight the importance of coastal erosion for potential carbon dioxide emissions. Key Points: Permafrost was incubated in seawater to determine the amount of CO2 potentially released by eroding permafrost coasts Observed CO2 production after 4 months is up to 4.3 ± 1.0 mg/gdw at 4 °C and comparable to release rates from thawing permafrost on land Permafrost coasts and nearshore waters are potentially an important source of CO2 that is neglected in carbon cycle budgets and models